Parametric Evaluation of Racking Performance of Platform Timber Framed Walls. (November 2017) - Dhonju, R.; D'Amico, B.; Kermani, A.; Porteous, J.; Zhang, B.
Abstract: This paper provides a quantitative assessment of the racking performance of partially anchored timber framed walls, based on experimental tests. A total of 17 timber framed wall specimens, constructed from a combination of materials under different load configurations, were tested. The experimental study was designed to examine the influence of a range of geometrical parameters, such as fastener size and spacings, wall length, arrangement of studs and horizontal members, as well as the effect of vertical loading on the racking strength and stiffness of the walls. The experimental results were then compared with results obtained from design rules, as given in the relevant European standards, to determine the racking performance of the walls, and are discussed in the paper.